Identification of Soil Fertility Constraints in Boranakunte-1 Micro-Watershed, Tumkur District, Karnataka - Veerendra Patel, S.S. Prakash, K.S. Rajashekarappa; M.C. Chaithra, T. Chikkaramappa*, G.G. Kadalli, G.M. (Journal of the Indian Society of Soil Science, 2021)
Land resource inventory of Boranakunte-1 micro-watershed (939 ha) representing central dry zone (Zone-4) of Tumkur district, Karnataka was carried out using geospatial techniques. Totally 140 surface soil samples at 250 m2 grid were collected, characterized for chemical and fertility properties and soil fertility maps were prepared using geographic information system (GIS). The results revealed that the soils were moderately alkaline (pH 8.29±0.47) with low total salt content (EC 0.15±0.10 dS m-1) and low to medium in organic carbon (OC) (0.50±0.20%) status. The available nitrogen (N), phosphorus (P) and potassium (K) contents were 238.9±48.8, 31.6±13.3 and 330.8±109.2 kg ha-1, respectively and the available sulphur (S) was 17.36±9.74 mg kg-1. The exchangeable calcium (Ca) and magnesium (Mg) were 21.62±6.32 and 10.82±3.35 cmol(p+)kg-1, respectively. The DTPA extractable iron (Fe), copper (Cu), manganese (Mn) and zinc (Zn) contents were 2.91±0.80, 0.90±0.32, 2.95±1.86 and 0.46±0.20 mg kg-1, respectively. The hot water extractable boron (B) content was 0.60±0.25 mg kg-1. Soil pH, OC, available N, P, Zn and B were found important soil fertility constraints for crop production in the micro-watershed. Thus, proper nutrient management along with correction of soil reaction and soil conservation measures needs to be done in order to enhance productivity.